Fundamental understanding of mechanical behavior of high-entropy alloys at low temperatures: A review. Issue 19 (14th October 2018) - Lyu, Zongyang; Fan, Xuesong; Lee, Chanho; Wang, Shao-Yu; Feng, Rui; Liaw, Peter K.
Abstract: Abstract : The basic principle of high-entropy alloys (HEAs) is that high mixing entropies of solid-solution phases enhance the phase stability, which renders us a new strategy on alloy design. The current research of HEAs mostly emphasizes mechanical behavior at room and higher temperatures. Relatively fewer papers are focused on low-temperature behaviors, below room temperature. However, based on the published papers, we can find that the low-temperature properties of HEAs are generally excellent. The great potential for cryogenic applications could be expected on HEAs. In this article, we summarized and discussed the mechanical behaviors and deformation mechanisms, as well as stacking-fault energies, of HEAs at low temperatures. The comparison of low-temperature properties of HEAs and conventional alloys will be provided. Future research directions will be suggested at the end.